2011
DOI: 10.1371/journal.pone.0027340
|View full text |Cite
|
Sign up to set email alerts
|

Internal Colonization of Salmonella enterica Serovar Typhimurium in Tomato Plants

Abstract: Several Salmonella enterica outbreaks have been traced back to contaminated tomatoes. In this study, the internalization of S. enterica Typhimurium via tomato leaves was investigated as affected by surfactants and bacterial rdar morphotype, which was reported to be important for the environmental persistence and attachment of Salmonella to plants. Surfactants, especially Silwet L-77, promoted ingress and survival of S. enterica Typhimurium in tomato leaves. In each of two experiments, 84 tomato plants were ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 63 publications
6
126
0
4
Order By: Relevance
“…In addition, bacterial aggregation or formation of biofilms can provide a protective layer, trap nutrients, and generally aid in stress tolerance (37)(38)(39). S. enterica biofilm mutants are significantly impaired in persistence on produce leaves (51,52). In support of the idea that biofilm formation is vital to S. enterica survival on leaves, we found that adrA and the production of exopolysaccharides, such as cellulose and colanic acid, contributed to persistence on alfalfa leaves (Fig.…”
Section: Figsupporting
confidence: 57%
“…In addition, bacterial aggregation or formation of biofilms can provide a protective layer, trap nutrients, and generally aid in stress tolerance (37)(38)(39). S. enterica biofilm mutants are significantly impaired in persistence on produce leaves (51,52). In support of the idea that biofilm formation is vital to S. enterica survival on leaves, we found that adrA and the production of exopolysaccharides, such as cellulose and colanic acid, contributed to persistence on alfalfa leaves (Fig.…”
Section: Figsupporting
confidence: 57%
“…At the preharvest stage, several potential routes for S. enterica colonization and internalization to contaminate tomato fruits have been examined previously (4)(5)(6)(7)(8). Some of the findings point to irrigation with contaminated water as a potential source of fruit contamination (4, 7); however, evidence that S. enterica is able to enter tomato plants through contaminated irrigation water remains inconsistent.…”
mentioning
confidence: 99%
“…Similarly, Salmonella enteric typhimurium internally colonizes tomato (Gu et al 2013; as well as lettuce (Klerks et al 2007) plants. On tomato, S. enterica has been reported to move systemically reaching fruits and seeds from leaves (Gu et al 2011). Once within the fruits, the pathogen can multiply to high densities (Gu et al 2011;Noel et al 2010).…”
Section: Bacteriamentioning
confidence: 99%
“…On tomato, S. enterica has been reported to move systemically reaching fruits and seeds from leaves (Gu et al 2011). Once within the fruits, the pathogen can multiply to high densities (Gu et al 2011;Noel et al 2010). A recent study demonstrated that Escherichia coli can internally colonize both leaves and roots of lettuce and spinach (Wright et al 2013).…”
Section: Bacteriamentioning
confidence: 99%